Characterization of a silicon nanowire array using reflected images captured by a smartphone camera. Issue 5 (3rd September 2021) - Lertvachirapaiboon, Chutiparn; Tunghathaithip, Naraphorn; Tungasmita, Sukkaneste; Baba, Akira; Shinbo, Kazunari; Kato, Keizo
Abstract: A practical technique for determining the length of a silicon nanowire (SiNW) array is reported by the analysis of reflected images from a smartphone camera. The SiNW array was prepared by electroless chemical etching and its length controlled by the etching time of a Si wafer. The average lengths for the SiNW array were characterized by scanning electron microscopy. The relationship between the reflection spectrum and the length of the SiNW array was investigated. The ratio of percent reflectance from 900 to 550 nm exponentially increased from 1.8 ± 0.1 to 22.2 ± 1.3 when the average length increased from 184 ± 12 to 1237 ± 23 nm. Optical sensing for characterization of the length of SiNW was further developed into a simple and practical technique using a smartphone camera as a detector. A 3D printed tool was assembled to the smartphone to control the light path and the reflected image of the SiNW array was acquired. The reflected intensity ratio obtained from the reflected images with long pass to short pass filters increased analogously to the spectroscopic results. This optical-sensing-based smartphone showed simple and rapid detection for determining the lengths of a SiNW array and a SiNW array coated with a polymer film. This platform is compact and capable of on-site detecting and is promising for the characterization of reflective materials.